Food-Associated Lactobacillus plantarum and Yeasts Inhibit the Genotoxic Effect of 4-Nitroquinoline-1-Oxide - Prete, Roberta; Tofalo, Rosanna; Federici, Ermanno; Ciarrocchi, Aurora; Cenci, Giovanni; Corsetti, Aldo (Frontiers in Microbiology, 2017)
Lactic acid bacteria (LAB) and yeasts, representing the prevailing microbiota associated with different foods generally consumed without any cooking, were identified and characterized in vitro for some functional properties, such as acid-bile tolerance and antigenotoxic activity. In particular, 22 Lactobacillus plantarum strains and 14 yeasts were studied. The gastro-intestinal tract tolerance of all the strains was determined by exposing washed cell suspensions at 37°C to a simulated gastric juice (pH 2.0), containing pepsin (0.3% w/v) and to a simulated small intestinal juice (pH 8.0), containing pancreatin (1 mg mL-1) and bile extract (0.5%), thus monitoring changes in total viable count. In general, following a strain-dependent behaviour, all the tested strains persisted alive after combined acid-bile challenge. Moreover, many strains showed high in vitro inhibitory activity against a model genotoxin, 4-nitroquinoline-1-oxide (4-NQO), as determined by the short-term method, SOS-Chromotest. Interestingly, the supernatants from bacteria- or yeasts-genotoxin co-incubations exhibited a suppression on SOS-induction produced by 4-NQO on the tester strain Escherichia coli PQ37 (sfiA::lacZ) exceeding, in general, the value of 75%. The results highlight that food associated microorganisms may reach the gut in viable form and prevent genotoxin DNA damage in situ. Our experiments can contribute to elucidate the functional role of food-associated microorganisms general recognized as safe (GRAS) ingested with foods as a part of the diet.